Reactivity of digermylenes toward potassium graphite : synthesis and characterization of germylidenide anions - Chia, Siew-Peng (2013)
The synthesis and characterization of the digermylenes [LGe–GeL] [L = L1 (3A), L2 (3B)] supported by the 2,6-diiminophenyl (L1) and 2-imino-5,6-methylenedioxylphenyl (L2) ligands are described. Their reactivities toward potassium graphite are also reported. The reaction of [LGeCl] [L = L1 (2A), L2 (2B)] with KC8 in tetrahydrofuran (THF) at room temperature afforded the digermylenes [LGe–GeL] [L = L1 (3A), L2 (3B)], which are the first examples of diaryldigermylenes stabilized by o-imino donor(s). The treatment of 3A with 2 equiv of KC8 in Et2O, followed by the addition of excess tetramethylethylenediamine (TMEDA), results in cleavage of the GeI–GeI bond to afford the germylidenide anion [L1GeK·TMEDA] (4A). Similarly, the reaction of 3B with excess KC8 in THF afforded the germylidenide anion [L2GeK] (4B). The molecular structures of compounds 4A and 4B as determined by single-crystal X-ray diffraction analysis show that the K atoms are η1-coordinated with the low-valent Ge atoms. Moreover, the negative charges at the Ge atoms in compounds 4A and 4B are stabilized by electron delocalization in the germanium heterocycles.